RASopathy in Patients With Isolated Sagittal Synostosis - Davis, Amani Ali (Glob Pediatr Health, 2019)
RASopathy is caused by dysfunction in the MAPK pathway, and include syndromes like Noonan syndrome (NS), NS with multiple lentigines (formerly known as Leopard syndrome), cardiofaciocutaneous (CFC), Legius syndrome, capillary malformation–arteriovenous malformation, neurofibromatosis type 1, and Costello syndrome. When counted together, RASopathies affect 1/1000 live births, and are characterized by cardiovascular manifestations, short stature, developmental delay, renal, urogenital, skin/skeletal abnormalities, and dysmorphic appearance. NS—one of the most common RASopathies—occurs in 1/1000 to 1/2500 live births. On the other hand, the frequency of CFC is unknown, but it is one of the rarest RASopathies, with estimates of only a few hundred cases worldwide. However, its phenotype overlaps with that of NS. In this case series, we describe 5 patients with a clinical and genetic diagnosis of RASopathy—either NS or CFC—all of whom were also diagnosed with isolated sagittal synostosis (ISS). Medical records from ophthalmology, cardiology, plastic surgery, medical genetics, cleft craniofacial, and neurosurgery were used to determine patient history. In our cohort, late presentation of ISS was the predominant form of ISS presentation. We hope this report further characterizes the burgeoning relationship between RASopathy and ISS. Furthermore, these findings support including sagittal synostosis among the presenting features in the clinical phenotype of RASopathies. Ethical approval was obtained from the university’s institutional review board.